METODE KOOPERATIF MODEL TEAM GAMES TOURNAMENT SEBAGAI ALTERNATIF MENINGKATKAN PRESTASI BELAJAR MATEMATIKA - Nurhasanah, Nurhasanah (Jurnal Pembelajaran Prospektif, 2020)
Mathematics is a study on the materials that has abstract objects and is built through a process of deductive reasoning, that is, the truth of a concept is obtained as the logical consequence of the truth that has previously been received, so the interrelationship concepts in mathematics are very strong and clear. In learning mathematics to be easily understood by students, the process of deductive reasoning is to strengthen the understanding that is already owned by students. Mathematics Learning objectives are training how to think systematically, logically, critically, creatively and consistently. While the objectives of this study are: (a) to know the improvement of students’ learning achievement after the application of the cooperative learning method of TGT model. (b) to know the effect of students’ learning motivation after the application of the cooperative learning method of TGT model. From the results of analysis obtained, it was revealed that the students’ achievement has increased from cycle I to cycle III that is, cycle I (66.67%), cycle II (77.78%), cycle III (88.89%). In conclusion, this research provides a positive effect onlearning motivation of Class V SDN 6 Parit Pelang students and this TGT model can be used as an alternative learning mathematics model.